2016
DOI: 10.2527/jas.2015-9373
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feed intake and dietary nutrient density on apparent ileal and total tract digestibility of nutrients and gross energy for growing pigs1

Abstract: The present study was conducted to investigate the effects of feed intake (FI) and dietary nutrient concentration on the determination of apparent ileal digestibility (AID) and apparent total tract digestibility (ATTD) of nutrients and GE for growing pigs. A total of 48 growing pigs (40.7 ± 1.3 kg initial BW) were surgically fitted with simple T-cannulas at the distal ileum and assigned to 6 treatment groups in a 2 × 3 factorial arrangement of 2 diets (a low-nutrient-density [LND] diet or a normal-nutrient-den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
0
6
0
2
Order By: Relevance
“…The different feed intakes may be a possible reason for the different effects of BW on the ATTD of nutrients (Shi and Noblet 1993;Morel et al 2006;Liu et al 2016). In addition, it was reported that the small intestine of pigs is almost fully developed at 20 kg BW, while the hindgut is still growing at 150 kg BW (Morel et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The different feed intakes may be a possible reason for the different effects of BW on the ATTD of nutrients (Shi and Noblet 1993;Morel et al 2006;Liu et al 2016). In addition, it was reported that the small intestine of pigs is almost fully developed at 20 kg BW, while the hindgut is still growing at 150 kg BW (Morel et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason is that the enhanced feed intake led to a faster passage rate in the gastrointestinal tract, allowing less time for fermentation in the hindgut, thus reducing the digestibility of all nutrients and energy [29]. Another possible explanation could be that the influence of endogenous excretions may be changed according to feeding levels [30]. However, other researchers observed no differences of ATTD of energy and nutrients in response to feeding levels [31,32], while Dourmad and coworkers even found that ATTD of DM, organic matter, and GE increased linearly with the increase of energy intake [33].…”
Section: Feed Intake Digestibility and Net Portal Fluxesmentioning
confidence: 99%
“…The organic matter (OM, %) content in the ingredients, diets, and feces was calculated as the difference between DM (%) and ash (%). The concentration of total carbohydrates (CHO, %) in the diets and feces was calculated according to the following equation (CHO = DM − CP − EE − ash) [38]. Neutral detergent fiber (NDF) and acid detergent fiber (ADF) were determined using filter bags and fiber analyzer equipment (Fiber Analyzer; ANKOM Technology, Macedon, NY, USA) following a modification of the procedures [39].…”
Section: Chemical Analysismentioning
confidence: 99%